Structural and rheological changes of texturized mung bean protein induced by feed moisture during extrusion. (15th May 2021) - Hossain Brishti, Fatema; Chay, Shyan Yea; Muhammad, Kharidah; Rashedi Ismail-Fitry, Mohammad; Zarei, Mohammad; Karthikeyan, Sivakumaran; Caballero-Briones, F.; Saari, Nazamid
Highlights: Mung bean protein (MBP) denaturation is critically affected by feed moisture. 49.3% feed moisture promotes partial protein unfolding and small aggregate formation. 49.3% feed moisture improves protein solubility, forming a strong gel network. 30.0 and 60.0% feed moisture cause complete denaturation and large aggregate formation. 49.3% feed moisture produces texturized MBP suitable as a meat extender. Abstract: Mung bean protein isolate was texturized at different feed moisture contents (30.0, 49.3, and 60.0%) at a constant temperature (144.57 °C) to evaluate the changes in protein profile, solubility, thermal, structural (at secondary and tertiary levels) and rheological properties. SDS-PAGE, surface hydrophobicity, circular dichroism, FTIR spectroscopy, and fluorescence analyses revealed protein unfolding, aggregation, and structural rearrangement as a function of feed moisture content. Extrusion at 49.3% feed moisture produced texturized mung bean protein (TMBP) with favourable partial denaturation, the formation of small aggregates, improved solubility, and digestibility with strong gel forming behaviour, whereas 30.0 and 60.0% moisture content resulted in complete protein denaturation, the undesirable formation of large aggregates and weak gels. In conclusion, protein denaturation and formation of aggregates can be controlled by manipulating feed moisture content during extrusion, with 49.3% feed moisture prompting favourable partial denaturation to produce TMBP with desirable qualities for use as a vegetarian-based meat extender.